2016
DOI: 10.1038/srep30443
|View full text |Cite
|
Sign up to set email alerts
|

Human DNA-Damage-Inducible 2 Protein Is Structurally and Functionally Distinct from Its Yeast Ortholog

Abstract: Although Ddi1-like proteins are conserved among eukaryotes, their biological functions remain poorly characterized. Yeast Ddi1 has been implicated in cell cycle regulation, DNA-damage response, and exocytosis. By virtue of its ubiquitin-like (UBL) and ubiquitin-associated (UBA) domains, it has been proposed to serve as a proteasomal shuttle factor. All Ddi1-like family members also contain a highly conserved retroviral protease-like (RVP) domain with unknown substrate specificity. While the structure and biolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
80
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(87 citation statements)
references
References 58 publications
(94 reference statements)
5
80
0
Order By: Relevance
“…On the other hand, the central part of Ddi1 encodes a highly conserved retroviral protease (RVP) domain with an HIV-like aspartic protease fold, emphasizing that Ddi1 is rather an unusual ubiquitin receptor Trempe et al, 2016). Consistent with the conservation of the RVP domain among eukaryotes, structural studies demonstrated that the Ddi1 dimer adopts a typical aspartic protease fold, strongly suggesting that the yeast and mammalian enzymes must be proteolytically active (Sirkis et al, 2006;Siva et al, 2016;Trempe et al, 2016). Although the Ddi1 proteolytic activity was previously addressed, it was not yet confirmed in vitro Trempe et al, 2016).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…On the other hand, the central part of Ddi1 encodes a highly conserved retroviral protease (RVP) domain with an HIV-like aspartic protease fold, emphasizing that Ddi1 is rather an unusual ubiquitin receptor Trempe et al, 2016). Consistent with the conservation of the RVP domain among eukaryotes, structural studies demonstrated that the Ddi1 dimer adopts a typical aspartic protease fold, strongly suggesting that the yeast and mammalian enzymes must be proteolytically active (Sirkis et al, 2006;Siva et al, 2016;Trempe et al, 2016). Although the Ddi1 proteolytic activity was previously addressed, it was not yet confirmed in vitro Trempe et al, 2016).…”
Section: Introductionmentioning
confidence: 95%
“…The RVP protease domain is the most conserved Ddi1 segment among eukaryotic orthologs, however its function remains the least understood. Structural analyses of the yeast and mammalian RVP domains strongly imply the presence of proteolytic activity, yet it has never been confirmed in vitro (Sirkis et al, 2006;Siva et al, 2016;Trempe et al, 2016). HDD is another evolutionally conserved domain with potential for DNA recognition based on its weak similarities to DNA binding domains .…”
Section: Ddi1 Function Depends On Its Putative Aspartic Protease Domainmentioning
confidence: 99%
“…Structure comparison of LmDdi1-RVP with yDdi1-RVP and hDdi2-RVP The crystal structure information on the RVP domain of Ddi1 is available from S. cerevisiae (PDB Code: 2I1A, 4Z2Z) [27,28] and human (PDB Code: 4RGH) proteins [29]. The reported structures are similar to LmDdi1-RVP, but the flap information is either missing or limited.…”
Section: Docking Studies With Hiv-1 Pr Inhibitorsmentioning
confidence: 99%
“…It adopts an extended b-sheet conformation and forms an antiparallel hydrogen bonding network with one part of the flap [28]. In hDdi2-RVP also, only one flap that interacts with the symmetryrelated molecule has a well-defined electron density [29]. These observations suggest that the flap of the Ddi1-RVP domain has a general characteristic of being more mobile and disordered compared to that of HIV-1 PR and its density is observed only when its mobility is restricted due to crystal packing.…”
Section: Docking Studies With Hiv-1 Pr Inhibitorsmentioning
confidence: 99%
“…In this study, we tested the sensitivity of a double-deleted yeast strain lacking WSS1 and DDI1 to DNA-damaging chemicals and identified a hypersensitivity to hydroxyurea, a ribonucleotide reductase inhibitor that induces nucleotide depletion and arrests cells in the S phase. Based on previous studies and our structural characterization of yeast and mammalian Ddi1/2 Siva et al 2016), we performed rescue experiments with various deletions and single-site mutants of Ddi1 ( Fig. 1B) to assess the involvement of particular yeast Ddi1 domains in the replication stress response.…”
Section: Introductionmentioning
confidence: 99%